2012
DOI: 10.1016/j.bbabio.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequence variation is associated with free-living activity energy expenditure in the elderly

Abstract: The decline in activity energy expenditure underlies a range of age-associated pathological conditions, neuromuscular and neurological impairments, disability, and mortality. The majority (90%) of the energy needs of the human body are met by mitochondrial oxidative phosphorylation (OXPHOS). OXPHOS is dependent on the coordinated expression and interaction of genes encoded in the nuclear and mitochondrial genomes. We examined the role of mitochondrial genomic variation in free-living activity energy expenditur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 144 publications
1
10
0
Order By: Relevance
“…Of particular interest are the CytB p.A191T and p.T194M substitutions located in the complex III Qi binding pocket, where quinone is reduced by cytochrome b [130]. We have shown that these substitutions are found in Health ABC participants in the lowest extreme of free-living activity energy expenditure [131]. The p.T194M, CytB variant occurs at a residue that is noted to undergo significant conformational changes upon contact with antimycin A, a pharmacological inhibitor of the Qi site [130].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest are the CytB p.A191T and p.T194M substitutions located in the complex III Qi binding pocket, where quinone is reduced by cytochrome b [130]. We have shown that these substitutions are found in Health ABC participants in the lowest extreme of free-living activity energy expenditure [131]. The p.T194M, CytB variant occurs at a residue that is noted to undergo significant conformational changes upon contact with antimycin A, a pharmacological inhibitor of the Qi site [130].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we extend our previous mtDNA work in the Health, Aging, and Body Composition (Health ABC) Study (Tranah et al, 2012b) by assessing dementia risk and cognitive decline in elderly African Americans, and by examining whether mtDNA variation is associated with circulating Aβ levels and markers of oxidative stress (plasma oxidized LDL and urinary 8-iso-prostaglandin F 2α ). We have shown that greater energy expenditure is associated with a reduced incidence of cognitive impairment in older adults from the Health ABC Study (Middleton et al, 2011) and have documented significant differences in metabolic rate among African and European mitochondrial haplogroups from this study (Tranah et al, 2011 and Tranah et al, 2012a). Considering the strong link between metabolic rate and cognitive impairment (Middleton et al, 2011), these previous studies provide the impetus for understanding the association between mitochondrial haplogroups and variants and cognition in late life.…”
Section: Introductionmentioning
confidence: 61%
“…We studied 138 Health ABC participants of European ancestry . Complete mtDNA was extracted from stored platelets collected at year 2 (1998‐1999) clinical follow‐up visit using the Gentra PureGene Kit (Qiagen, Hilden, Germany) and sequenced using the Affymetrix Mitochondrial Resequencing Array 2.0 (MitoChip, Affymetrix, Santa Clara, California) as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…We studied 138 Health ABC participants of European ancestry . Complete mtDNA was extracted from stored platelets collected at year 2 (1998‐1999) clinical follow‐up visit using the Gentra PureGene Kit (Qiagen, Hilden, Germany) and sequenced using the Affymetrix Mitochondrial Resequencing Array 2.0 (MitoChip, Affymetrix, Santa Clara, California) as previously described . The MitoChip interrogates the forward and reverse strands of the 16.5‐kb mitochondrial genome for a total of approximately 30‐kb sequence, enables the detection of known and novel mutations, and has redundant probe tiling for detecting the major human mitochondrial haplotypes and known disease‐related mutations.…”
Section: Methodsmentioning
confidence: 99%